Karakterisasi polyester komposit berpenguat serat pohon pisang saba dengan filler carboxyl terminated butadiene acrylonitryle sebagai material bumper otomotif - Sujita, S.; Sulistyowati, E. D.; Zainuri, A.; Sinarep, S.; Pandiatmi, P. (Universitas Mataram, 2022)
The bumper is one part of the vehicle that has a very important role. In addition to functioning as aerodynamics and aesthetics to attract consumers, the bumper also functions as a damper and a buffer against impact (shock/impact force) in the event of an accident. Therefore, the material used as the bumper, especially the rear bumper, is often damaged, so a material that has good tensile strength and impact toughness is needed. In this research, the object of the research is the polyester matrix composite. The research aspect is more emphasized on the effect of using Musa acuminata stem fiber (MASF) as a reinforcement and filler of Carboxyl Terminated Butadiene Acrylonitryle (CTBN) on changes in tensile strength and impact toughness. The results of the study show. the addition of MASF volume fraction and CTBN filler increased the tensile strain, impact toughness, impact energy, but decreased the tensile strength of the polyester matrix composite material. The change in mechanical properties is due to the bonding of MASF with CTBN and polyester with CTBN, so that the impact toughness and ductility of the specimen increases, because CTBN is elastic.